Využití Lean Six Sigma projektové metodologie v oblasti financí v mezinárodní společnosti - Hudáková, Lucia (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Diplomová práce se zabývá analýzou využití projektové metodologie Lean Six Sigma na finančním oddělení ve vybrané mezinárodní společnosti a návrhem postupu na jeho zlepšení. Jsou zde obsaženy teoretické poznatky týkající se metody Lean Six Sigma jako i praktická ukázka použití dané metody v praxi. Na základě údajů a zkoumání použití metody je provedená analýza efektivního využití. Následně je popsané zhodnocení dané analýzy a navržen postup pro zlepšení situace do budoucna.

The master’s thesis deals with an analysis of Lean Six Sigma Project approach used by financial department in chosen multinational company. A proposal for improvement of using LSS in the future is placed in the thesis as well. The thesis contains theoretical knowledge about LSS as well as sample of using this method in real. An analysis of its effective usage is provided based on data and investigation right from the company using LSS. In the end there is evaluation of the analysis as well as proposal of future process for improvement in using LSS.
Lean Six Sigma Project Approach in Finance Department of Multinational Company
Keywords: Lean Six Sigma; finance; mezinárodní společnost; Lean Six Sigma; finance; international business company